(untitled) (REICE: Revista Electrónica de Investigación en Ciencias Económicas, 2015)
Analyze the possibility and the socioeconomic impact, to an official dollarization in Nicaragua. The inductive-deductive method which allows to apply the theory inquired into, for extensive information of this phenomenon was used for conducting this test. From the deduction having this problem at the country level, the expectations would before an official exchange was assessed. This work also integrates the analytical method, which takes into account the main sectors of the Nicaraguan economy, which are dollarized, so that they can provide possible suggestions. Nicaragua has a high level of unofficial dollarization, approximately 70% and the most affected is the working class who receive their salaries in cords, causing every day greater loss of purchasing power on goods and services purchased. It is very difficult to leave the Nicaragua Cordoba by the dollar, because it has enough cash reserves, it is best recordobizar our economy with higher labor productivity, increased efficiency in the economy and transmit more confidence on the part of the Nicaraguan population to our local currency. DOI: http://dx.doi.org/10.5377/reice.v2i4.1732 REICE Vol. 2, No. 4, julio-diciembre 2014: 159-177